2013
DOI: 10.1002/jbm.a.34613
|View full text |Cite
|
Sign up to set email alerts
|

Surface projections of titanium substrates increase antithrombotic endothelial function in response to shear stress

Abstract: Despite the therapeutic benefits of both mechanical circulatory assist devices and nitinol stents with titanium (Ti) outer surfaces, problems remain with thrombosis at the blood-contacting surface. Covering these surfaces with a layer of endothelium would mimic the native lining of the cardiovascular system, potentially decreasing thrombotic complications. Since surface topography is known to affect the phenotype of a seeded cell layer and since stents and ventricular assist devices exhibit surface protrusions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…The non‐significant increase in the expression level of these genes was likely due to the large coefficients of variation, which may reflect the range of shear stresses to which the ECs were exposed to on the stent struts. This notion was supported by other study demonstrating much smaller coefficients of variation in COX‐2 and KLF‐2 gene expression when ECs were exposed to flow on a planar Ti surface …”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The non‐significant increase in the expression level of these genes was likely due to the large coefficients of variation, which may reflect the range of shear stresses to which the ECs were exposed to on the stent struts. This notion was supported by other study demonstrating much smaller coefficients of variation in COX‐2 and KLF‐2 gene expression when ECs were exposed to flow on a planar Ti surface …”
Section: Discussionsupporting
confidence: 72%
“…This notion was supported by other study demonstrating much smaller coefficients of variation in COX-2 and KLF-2 gene expression when ECs were exposed to flow on a planar Ti surface. 24 The level of eNOS gene was downregulated after exposure of the cell-seeded stents to flow, but the secretion of NO as indicated by nitrite levels increased. In our previous work, we have observed that exposure of blood-derived and aortic hECs to flow shear stress (15 dyne/cm 2 for 24 h) caused an overall increase in eNOS gene expression.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, spatially arranged micron and submicron titanium features have been demonstrated to modulate vascular cell behavior. 15,16 Among the various choices of metallic materials, titanium-based alloys are the promising candidates for vascular intervention applications because of their excellent corrosion resistance, biocompatibility and mechanical properties [17][18][19] where corrosion resistance and biocompatibility mainly results from the TiO 2 passivation layer. [20][21][22] A thin layer of TiO 2 has also been shown to improve blood compatibility when coated on stainless steel.…”
Section: Introductionmentioning
confidence: 99%